Gender accounting of consumption and the life-cycle deficit for india - Laishram Ladusingh (Asia-Pacific Population Journal, 2014)
In the present paper, labour income, consumption and the life-cycle deficit (LCD) by gender for India is considered. From the individual’s perspective, private and public consumption for education, health and other goods and services has been taken into account. For either sex, the share of public consumption is about 17 per cent of the total consumption for health, education and others. Throughout the life cycle, the per capita annual labour income of a woman is lower than that of a man; even at the peak age of earning, it is only about one-sixth of a man’s per capita labour income at the corresponding age. Though a male consumes more for health, education and other goods and services, the gender gap is not as wide as that of income from labour. At the per capita level, a male experiences a monetary surplus during the working age range of 20 to 64 years and faces a life-cycle deficit only before entering the labour market and during old age, but a female must deal with a life-cycle deficit all through the life cycle.